The Focal easy guide to Flash MX 2004 : for new users and professionals - Hosea, Birgitta (Focal easy guide series., 2004)
Confused by ActionScript? Want to get to grips with creating interactive graphics and animation in Flash quickly? Whether you are a new user or a professional illustrator, designer or animator experienced in other animation and effects packages, this highly visual, color book will be all you need to get you up and running with the latest powerful upgrade - Flash MX 2004. Birgitta Hosea uses tried and tested material based on her teaching, breaking down the software into its main components and providing lots of screenshots and simple step-by-step instructions. This encourages you to get the most out of the programme and fully develop your skills, whilst allowing those with particular needs to 'jump ahead'. The structure and style, influenced by her commercial and creative expertise, allows you either as a student or professional to dip in and out according to the needs of your specific projects, but also allows the exploration of the programmes capability when you have more time.